Sentidos da participação de pais e mães no nascimento de seus filhos - Nogueira, Nyessa Souza Arantes (2016)
In the process of motherhood and fatherhood, Childbirth is a significant point. It is beyond a physiological act, it is an event built and developed in a social and cultural context. Throughout history, the birth of a baby has distanced him from the family and became an artificial and complex process. Nowadays the parents are feeling increasingly incapable to decide anything about their childbirth, due the procedures of obstetrical care providers, which are felling as on the right to take ownership of childbirth even to take their babies as a property of the institution. Woman deprives confidence in their ability to give birth and men the right to attend the birth of his son. Therefore, recognizing the complexity of this phenomenon, this study aimed to understand the meanings produced by mothers and fathers about their participation in the birth of their children. Eight couples dwelling in the city of Uberlandia (MG) were interviewed. Two researches were taken. Semi-structured individual interviews were conducted, one before delivery and another after it. The analysis was based on a qualitative perspective, social constructionist nature, research of the construction process of meanings from a thematic analysis, being organized into four categories: 1) Expectations for delivery; 2) the expectations to the reality experienced in childbirth; 3) Post-partum period and 4) Obstetric Violence. Regarding expectations for childbirth, parents showed a sense of unknown anything of they were about to face ahead, and bring out your insecurities, fears, anxieties, hopes and belief that all would be well. As the experiences in childbirth were been taken, It was predominantly marked by disrespect and violence to the parents and baby, taken by the health professionals who attended them. Mom and her baby taken as ownership of the institution and mostly seen as subjects, both, mom and baby, lacked of subjectivity and rights. As the post-partum arrive, a difficult adaptation and professional helplessness was observed for most couples, struggling to cope with basic needs of the baby, such as exclusive breastfeeding. Finally, on the whole experience of mothers and fathers in the care of pregnancy and childbirth, it was apparent intersections of violence as a mark of attention to obstetric and neonatal health, it is necessary to alert the public and health authorities for urgent measures to change this situation. However, it was noted the need for a critique that goes beyond the normative and cultural discourses that suggest a mismatch between the health system and its obstetric care and the current scientific evidence and public policy. It is also necessary to question the lack of supervision to the already existing laws, besides the lack of pregnant women and their families about their rights. Thus, the debate deepens, establishing itself on the lack of opportunity for informed choices and the limited presence of qualified information for pregnant women and their families. In addition to providing information to women, professionals need to take an approach of posture, care, respect and commitment to the most recent scientific evidence, in order to assist in overcoming taboos related to maternal and child care.